Risiko Produksi Cabai Merah Besar Pada Berbagai Luas Garapan Usahatani - WIDYANTARA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Production Risks of Big Red Chillies in Various Land Farming Areas Big red chili is one kind of chillies which are much needed by the people of Indonesia, so that this commodityhas a high economic value. With the chili consumption of 1.4 kg per capita per year, domestic production cannot meet this demand, so the price of chillies in the market varies widely. On the farming side, farmers experience uncertainty caused by climatic factors and other factors of chilli cultivation. The goal of this study was t identify: the productivity of various land sizes, to know the optimal  areas of big red chilli farming,  and the susceptibility or the gravity of the risk of chilli farming production. The results showed that the wider areas tend to have lower and lower productivity. The optimal chilli farming land area was 31.59  are. The production risks which were most vulnerable was experienced by farmers who had land areas between 21 and 30 ares while narrower farming areas were not susceptible to risks.
Keywords: big red chili; production risk; land farming